7th Euro Evo Devo meeting: Report on the "Evolution of regeneration in Metazoa" symposium. Issue 2 (28th August 2019) - Gazave, Eve; Röttinger, Eric
Abstract: Regeneration, the ability to restore lost parts of the body, is a widespread phenomenon in animals. While this ability is somehow limited in classical developmental model organisms, a variety of animals are able to regenerate complex structures such as limbs or important parts of their body, upon injury. Despite the recent emergence of regenerative studies using a large variety of metazoans, we still lack a general view of the evolution of animal regeneration. In the context of the 7th EvoDevo meeting that took place in June 2018 in Galway, Ireland, the "Evolution of regeneration in Metazoa" symposium gathered scientists studying the regenerative potential of evolutionarily distant animal species. Abstract : Regeneration, the ability to restore lost parts of the body, is a widespread phenomenon in animals. While this ability is somehow limited in classical developmental model organisms, a variety of animals are able to regenerate complex structures such as limbs or important parts of their body, upon injury. Although the recent emergence of regenerative studies using a large variety of metazoans, we still lack a general view of the evolution of animal regeneration. In the context of the 7th EvoDevo meeting that took place in June 2018 in Galway, Ireland, the "Evolution of regeneration in Metazoa" symposium gathered scientists studying the regenerative potential of evolutionary distant animal species. This symposium was dedicated to the morphological, cellular, and molecular mechanisms underlying regeneration in a variety of models that are representative of the metazoan diversity and that are particularly suited to address given questions of interest. Beyond this phyletic consideration, several types of regeneration (whole body, appendages, organ, tissue) were presented and emphasized. A specific attention was given to the identity, plasticity, and differentiation potential of the cells required for the regeneration processes. In addition, the symposium encompassed different scientific approaches and techniques, such as comparative transcriptomic, morphological, molecular and functional assays, genetic lineage‐tracing and live imaging, to efficiently address this regeneration topic. Research Highlights: The "Evolution of regeneration in Metazoa" symposium took place during the 7th EvoDevo meeting in Galway (IRL). It gathered scientists studying the cellular and molecular mechanisms underlying regeneration of evolutionary distant animal species